Creating Spaces for Transformative Civic Engagement in Higher Education - Felipe A. Filemeno (The University of Alabama, 2022)
Review of the book: Maria Avila, Transformative Civic Engagement Through Community Organizing. Sterling, VA: Stylus, 2018, 136 pages. ISBN: 978-1-62036-104-7